Sorghum yield response to NPKS and NPZn nutrients along sorghum-growing landscapes. (11th March 2022) - Desta, Gizaw; Amede, Tilahun; Gashaw, Tadesse; Legesse, Gizachew; Agegnehu, Getachew; Mekonnen, Kindu; Whitbread, Anthony
Summary: Grain sorghum [Sorghum bicolor (L.) Moench] is the major cereal crop used as staple crop in the arid and semi-arid regions of Ethiopia. Low sorghum yields are attributed to soil, climate and topographic factors. We investigated sorghum yield response to factorial combination of nitrogen and phosphorous (NP) as well as potassium (K), sulphur (S) and zinc (Zn), and how the position of farmers' fields belonging to different landscape positions (i.e., upslope, mid-slope, and foot slope) could explain fertilizer response and yield variability. The analysis in this study made use of dataset from two sets of on-farm experiments where trials were set at two farmers' fields for NPKS and three farmers' fields for NPZn experiments in each landscape position. The experiments were implemented at two sorghum-growing locations (i.e., Hayk and Sirinka) in parts of the north-eastern Amhara region in Ethiopia. Sorghum yield response to fertilizer application was strongly linked to the spatial variation along landscape positions and varied over locations. Fertilizer response was significantly higher at foot slopes compared to mid-slopes and upslope positions, where fields at foot slopes exhibited relatively homogeneous responses. Application of combined nitrogen (N) and phosphorus (P) fertilizers, landscape position and the interaction of fertilizer application and landscape positions strongly affected sorghum yield. There was a linear and significant increase in sorghum yield with the increase in the NP rates. The combined application of NP with different levels of KS as well as NP with Zn fertilizer rates did not result in significant yield difference. The results indicated that local factors were much more influential when accounting for the heterogeneity in sorghum yield response to fertilizer. This further acknowledges the importance of a landscape-based fertilizer management approach to respond yield potential variability related with the farmers' fields and landscape environment. Further investigation is needed to develop homogeneous fertilizer response units based on spatial variability of soil and topographic attributes along the landscape.